Influence of Repetitively Pulsed Negative Bias Parameters on Macroparticle Surface Density - Ryabchikov A. I. Aleksandr Ilyich; Sivin D. O. Denis Olegovich; Bumagina A. I. Anna Ivanovna; Shevelev A. E. Aleksey Eduardovich; Shulepov I. A. Ivan Anisimovich; Ananin P. S. Petr Semenovich (2016, 2016)
Title screen